Conceptualizing "Rural" for Research in Education: A Sociological Perspective - William H. Whittaker (Journal of Research in Rural Education, 1983)
The lack of consensus on the denotation of "rural" in educational and social work research makes generalizability of findings problematic. This paper reviews definitional problems related to occupational, sociocultural, ecological and multi-dimensional conceptions of rurality. Multi-dimensional typologies developed by the U.S. Department of Agriculture's Economic Research Services and the Maine State Planning Office are described and recommended.